Tawhid String Relation and Itsar Concept of Islamic Bank in Information Technology and Competitive Advantage Issues - Badawi, Ahmad; Utami, Wiwik; Kurniasih, Augustina; Marsoem, Bambang Santoso (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The current Covid-19 pandemic phenomenon that has shaken the world economy, including Indonesia, has caused social problems, including the increasing number of poor people. The purpose of this conceptual paper is to conduct a study related to the business model of Islamic banks, which is based on the Tawhid String Relations concept and is managed with the Itsar concept that can contribute to helping overcome social problems in alleviating poverty. The method used is the literature review. Social instruments, product innovation, and Islamic banking services are aimed at the benefit of the community. Also, the management of Islamic banks should be oriented towards managing Islamic banks to get Allah's pleasure, which is to provide benefits to the ummah.